Strategi Koping Pada Ibu Dengan Anak Berkebutuhan Khusus - Ima Sukmawati (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2020)
ABSTRACT Children who experience obstacles in their development are known as children with special needs (ABK). ABK is one of the stressors, especially mothers, where the response must be balanced with coping strategies. This study aims to describe coping strategies in mothers with children with special needs. The method used was descriptive with purposive sampling or judgment sampling technique, the total sample was 62 respondents from a total population of 168 respondents. The results showed that the coping strategy in mothers with special needs in Ciamis State Special School was an adaptive coping strategy of 42 respondents (56.5%). While the description of the types of coping strategies used by problem focused coping were 32 respondents (51.6%). The conclusion of this study is that the coping strategy of mothers with special needs in Ciamis State Special School is adaptive to the type of problem focused coping coping strategy. Keywords: Coping Strategy, Mother, Children with Special Needs